Decoding the Intellectual and Influential Dynamics of Structural Capital: A Multidimensional Bibliometric Analysis - Imad Al Zeer; Hala Alsabatin; Weam Tunsi; Nidal Al-ramahi (Decision Making: Applications in Management and Engineering, 2024)
Structural capital is a critical element in fostering innovation and competitive advantage within the rapidly evolving domain of organisational knowledge management. This study explores the intellectual and influential dimensions of structural capital by providing quantitative insights complemented by an extensive literature review. It seeks to elucidate the field's core intellectual framework and identify the key contributors shaping its development. The research examines 54 articles and review papers sourced from the Scopus database spanning the period 1997 to 2023, employing an innovative mixed-method approach to bibliometric citation analysis. Advanced analytical tools, including R Studio, VOS viewer, and Microsoft Excel, were utilised to systematically analyse the data and perform complex bibliometric tests, thereby offering a detailed understanding of the structural capital research landscape. The findings highlight the prominent journals, authors, and collaborative networks that have significantly influenced the field. Notably, the *Journal of Intellectual Capital* emerges as a pivotal platform for academic discourse on structural capital. The study categorises structural capital into six principal domains: business operations and human resource management, organisational dynamics and innovation, industry performance and innovation, financial strategies and human capital, intellectual capital and risk management, and technology and innovation through structural capital. In addition to identifying substantial gaps in the existing literature, the study proposes future research directions, thereby laying a foundation for further empirical inquiry. This research represents a pioneering effort in applying bibliometric methodologies to the study of structural capital. Its findings and pro-posed research avenues provide a robust framework for both practitioners and scholars, contributing meaningfully to the advancement of knowledge in the field.